(untitled) (Quinto Sol, 2015)
Throughout the 19th century, in the context of setting up the new republican order, the humanization of physical punishments was promoted. As part of a cultural climate affected by the individualization of the body, modern educational trends questioned the excessive punishment of children. This paper discusses the reviews of such disciplinary practices in Buenos Aires elementary schools and its countryside, with the aim of reflecting on how this “civilized awareness” process struggled for a punishment economy to design –at the end of the century– a new ethical code of honor and virtue based on self-discipline as the kind of behavior that should be adopted by future citizens of the republic.